Direct Deoxygenative Intramolecular Acylation of Biarylcarboxylic Acids - Li, Yantao; Xu, Wentao; Zhu, Chengjian; Xie, Jin (Synlett, 2021)
A photocatalyzed intramolecular cyclization is developed for the synthesis of fluorenones. In this photoredox reaction, triphenylphosphine is used as an inexpensive and effective deoxygenative reagent for biarylcarboxylic acids to give acyl radicals, which quickly undergo intramolecular radical cyclization. Reactions in the presence of air and continuous flow photoredox technology demonstrate the generality and practicality of this process.
Keywords: photocatalytic; deoxygenation; triphenylphosphine; radical cyclization; flow chemistry